ANALISIS KESALAHAN SISWA KELAS X DALAM MENYELESAIKAN PERMASALAHAN FUNGSI EKSPONEN DITINJAU DARI GENDER - Topa, Siti Il; Setiawani, Susi; Oktavianingtyas, Ervin (Department of Mathematics Education , University of Jember, 2018)
ABSTRACT. Mathematics is a lesson related to numbers and geometry. Students often have difficulty in solving problems, so that in this research at analysis of error in grade X students of Jenggawah Senior High School to solving the mathematical problem exponent function material, based on the conceptual error consisting of 8 indikators, principle error 6 indikators, and 1 operation error reviewed from gender. The intended gender is male and famale gender. This research is a qualitative research with a descriptive approach, the subjects in this research were male and famale students those taken randomly using the snowball sampling method, so that 4 subjects were analyzed. Students are given questions and then interviewed to get more accurate information. The result of the research show that male students experience errors in several types of concept indikators, principal, and operation. Furthermore, famale student only experience error in indikators of concept and principle. On operation errors, famale students do not experience error. Keywords: error analysis, exponen function, gender.